Microstructural basis for improved corrosion resistance of laser surface processed AZ31 Mg alloy. (October 2021) - Jana, Saumyadeep; Olszta, Matt; Edwards, Danny; Engelhard, Mark; Samanta, Avik; Ding, Hongtao; Murkute, Pratik; Isgor, O. Burkan; Rohatgi, Aashish
Highlights: Mg alloy (AZ31) shows better corrosion resistance after laser surface processing. Laser surface processing changes mode of corrosion from localized to uniform. Laser surface processing creates ∼0.5 μm thick mixed-metal oxide surface film. Mixed-metal oxide surface film converts to layered double hydroxide film later. Abstract: Despite their excellent strength-to-weight ratio, wider use of magnesium (Mg) alloys for light-weight applications is limited by their poor corrosion resistance, especially in chloride-containing environments. The present study shows improved corrosion resistance imparted by laser surface processing (LSP) of a commercial AZ31 (Mg-3Al-1Zn) alloy. Nanosecond laser processing at three different power settings was carried out on the surface of a 1-mm-thick rolled AZ31 sheet. Electrochemical studies and salt spray testing (ASTM B117) indicate substantial enhancement of corrosion resistance in LSP-treated AZ31. The underlying reasons behind improved corrosion resistance of the LSP-AZ31 surface have been studied through detailed microstructural characterization and chemical analysis by SEM, TEM, and XPS. Formation of a ∼0.5 μm thick mixed metal (Mg, Al) oxide surface film, together with refinement in the size and number density of Al-Mn intermetallic particles, are shown to play a major role toward improved corrosion resistance after LSP treatment of the AZ31 alloy.